(untitled) (Research, Society and Development, 2020)
Introduction: Studies have suggested that pentraxin 3 (PTX3) and Mannose Binding Lectin (MBL) may interfere with cognitive processes. Objective: Identify data reported in the literature involving cognition, PTX3 and MBL. Materials and Methods: The research was done in five databases and the selection of studies was performed in two stages. The first involved review of titles and abstracts. Then the full articles were read and those that did not meet the eligibility criteria were excluded. Results: A total of 3,097 titles and abstracts were selected, but 3,089 were excluded. Finally, 8 articles were included in the review. The articles pointed out that high levels of PTX-3 could be predictors of cognitive impairment while high levels of MBL could have a protective effect on cognition. Conclusion: The current studies are still contradictory and inconclusive, but they lead us to reflect on possible genetic influences of innate immunity in the Central Nervous System. Further research involving the effects of PTX-3 and MBL and its variants on cognition are necessary.